2013
DOI: 10.4103/0976-237x.123047
|View full text |Cite
|
Sign up to set email alerts
|

Comparative distribution of Lysyl Oxidase (G473A) and NQO1 (C609T) polymorphism among tea-garden workers (habitual chewers of betel quid) of Darjeeling district and Kolkata city of West Bengal

Abstract: Context:Chewing of processed arecanut products with tobacco and betel quid has been attributed to many oral pathological conditions. These products are very popular among the youngsters of lower economic groups. Genetic predisposition has been now identified as a major risk factor for increasing the susceptibility toward the disease among these chewers.Aims:Our study mainly aims to find out the predisposition of LOX (G473A) and NQO1 (C609T) polymorphisms and present a comparison between the population (habitua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…The prevalence of the minor T allele varies among ethnic groups (4-20%), with the highest prevalence occurring in Asian populations [14][15]. In one of our previous observational studies, we found a very high prevalence of NQO1 Pro>Ser polymorphism among both urban and rural populations of West Bengal, India, who were habitually exposed to processed areca nut and smokeless tobacco [16]. This study explores the effect of NQO1 Pro>Ser polymorphism in increasing susceptibility to Oral Submucous fibrosis among habitual areca nut and smokeless tobacco chewers.…”
Section: Association Of Nqo1 C609t (Pro187ser) With Risk Of Oral Submucous Fibrosis In Eastern Indian Populationmentioning
confidence: 67%
“…The prevalence of the minor T allele varies among ethnic groups (4-20%), with the highest prevalence occurring in Asian populations [14][15]. In one of our previous observational studies, we found a very high prevalence of NQO1 Pro>Ser polymorphism among both urban and rural populations of West Bengal, India, who were habitually exposed to processed areca nut and smokeless tobacco [16]. This study explores the effect of NQO1 Pro>Ser polymorphism in increasing susceptibility to Oral Submucous fibrosis among habitual areca nut and smokeless tobacco chewers.…”
Section: Association Of Nqo1 C609t (Pro187ser) With Risk Of Oral Submucous Fibrosis In Eastern Indian Populationmentioning
confidence: 67%